The Impact of Administrative Leadership on Job Satisfaction of Employees in Lebanese Banks - Aljammal, Naji; Abbass, Ahmad Kamel (The Arab Journal of Administration, 2025)
This study highlights the impact of different management leadership styles on job satisfaction among employees working in Lebanese banks, using a descriptive-analytical approach to analyze the relationship between these various styles and employee satisfaction. The study primarily relied on the use of a questionnaire as the primary tool for data collection. The study focused specifically on exploring the impact of four main leadership styles: democratic leadership, autocratic leadership, laissez-faire leadership, and transformational leadership. Data was collected from 210 banking employees working in seven central banks in Lebanon. The statistical analysis results showed that democratic leadership and transformational leadership have a substantial and statistically significant positive impact on job satisfaction. This result indicates that leadership styles that encourage participation and effective communication and enhance the development of skills and positive attitudes among employees improve their satisfaction level. In contrast, the autocratic leadership style did not significantly impact job satisfaction, suggesting that this approach, which relies on individual decisions and central control, may need to be revised in the Lebanese banking context. As for free leadership, the study showed a positive relationship between it and job satisfaction, although it requires precise implementation to ensure its effectiveness, or it may lead to adverse outcomes. The study concludes with recommendations for Lebanese banks to adopt democratic and transformational leadership practices that have proven effective in improving employee satisfaction while reducing reliance on autocratic leadership. It also recommends cautiously managing the free leadership application to ensure its positive impact on employee satisfaction and enhance overall organizational performance.